2017
DOI: 10.1515/jomb-2016-0030
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction Markers in Low Cardiovascular Risk Individuals: Comparison of Males and Females

Abstract: SummaryBackgroundCardiovascular diseases (CVD) account for approximately 50% of the total deaths in Turkey. Most of them are related with atherosclerotic coronary heart disease. Predictive value of endothelial dysfunction markers related with the earliest stage of atherosclerosis has been getting more attention. We hypothesized that differences in endothelial dysfunction biochemical markers among genders would aid to capture proatherogenic activity that was not diagnosed by conventional risk assessment scoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
7

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 52 publications
0
10
0
7
Order By: Relevance
“…Accumulating evidences suggested that endothelial dysfunction was one of the critical determinants in pathogenesis of atherosclerotic cardiovascular disease, and angiocardiopathy such as myocardial infarction, stroke, and vascular remodeling was independently associated with endothelial dysfunction [23][24][25][26]. Oxidative stress, inflammatory response and active material imbalance are involved in the progress of vascular endothelial injury [27].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences suggested that endothelial dysfunction was one of the critical determinants in pathogenesis of atherosclerotic cardiovascular disease, and angiocardiopathy such as myocardial infarction, stroke, and vascular remodeling was independently associated with endothelial dysfunction [23][24][25][26]. Oxidative stress, inflammatory response and active material imbalance are involved in the progress of vascular endothelial injury [27].…”
Section: Discussionmentioning
confidence: 99%
“…Помимо этого, NO тормозит агрегацию тромбоцитов, адгезию лейкоцитов, инфильтрацию и пролиферацию гладкомышечных клеток сосудов. NO препятствует окислительной модификации ЛПНП [10].…”
Section: обзоры §unclassified
“…Не потеряла актуальности и точка зрения, что ЭД -это системное расстройство, характеризующееся прежде всего снижением выработки NO, патологическое состояние, ухудшающее сосудистый гомеостаз и приводящее к потере защитных свойств эндотелиальных клеток [6][7][8][9][10]. В противовес NO, как вазодилататору, в организме вырабатывается мощный вазоконстриктор -ЭТ-1 или в ряде литературных источников просто ЭТ [2,4,12].…”
Section: обзоры §unclassified
See 1 more Smart Citation
“…e VWF is synthesised in endothelial cells and is then stored. It mediates platelet aggregation and adhesion [3]. It carries factor VIII in circulation and mediates initial platelets that stick to the sub endothelium following vascular endothelial damage as a result of hyperlipidaemia, smoking, or hypertension [4,5].…”
Section: Introductionmentioning
confidence: 99%